Evidence for a negative Pasteur effect in articular cartilage. - Lee, R; Urban, J (1997)
Uptake of external glucose and production of lactate were measured in freshly-excised bovine articular cartilage under O2 concentrations ranging from 21% (air) to zero (N2-bubbled). Anoxia (O2 concentration < 1% in the gas phase) severely inhibited both glucose uptake and lactate production. The decrease in lactate formation correlated closely with the decrease in glucose uptake, in a mole ratio of 2:1. This reduction in the rate of glycolysis in anoxic conditions is seen as evidence of a negative Pasteur effect in bovine articular cartilage. Anoxia also suppressed glycolysis in articular cartilage from horse, pig and sheep. Inhibitors acting on the glycolytic pathway (2-deoxy-D-glucose, iodoacetamide or fluoride) strongly decreased aerobic lactate production and ATP concentration, consistent with the belief that articular cartilage obtains its principal supply of ATP from substrate-level phosphorylation in glycolysis. Azide or cyanide lowered the ATP concentration in aerobic cartilage to approximately the same extent as did anoxia but, because glycolysis (lactate production) was also inhibited by these treatments, the importance of any mitochondrial ATP production could not be assessed. A negative Pasteur effect would make chondrocytes particularly liable to suffer a shortage of energy under anoxic conditions. Incorporation of [35S]sulphate into proteoglycan was severely curtailed by treatments, such as anoxia, which decreased the intracellular concentration of ATP.